Pipeline Steels for Sour Service - Shabalov, Ivan.; Matrosov, Yury.; Kholodnyi, Alexey; Matrosov, Maxim; Velikodnev, Valery; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book summarizes the results of experimental work on the development of technologies for the manufacture of sour service line pipe steels. It presents the latest theories on the mechanisms of cracking and factors affecting fracture resistance in H2S-containing media of low-alloy pipe steels. The authors propose methods for improving the quality of continuously cast slabs and show the effect of the chemical composition on the microstructure and properties of rolled plates for pipes. Considerable attention is paid to the metallurgical aspects of microstructure formation and its mechanical properties, as well as the enhancement and cracking resistance of sour service sheets under thermomechanical rolling with accelerated cooling. In brief, the book presents a cutting-edge overview of sour service sheet and pipe production.
The Impact of Hydrogen Sulphide-Containing Media on Pipe Steels -- Factors Affecting Resistance of Pipe Steels to Cracking in H2S-Containing Media -- Central Segregation Chemical and Structural Heterogeneity in Continuously Cast Slabs -- Structure and Properties Formation of Pipe Steels under Thermomechanical Processing with Accelerated Cooling -- Influence of the Chemical Composition and Thermomechanical Processing on the Plates Centerline Segregation Heterogeneity and Resistance to Hydrogen Induced Cracking -- State of the Sour Service Sheets and Pipes Production Technology.
Keywords: Metals; Materials; Industrial engineering; Production engineering; Metals and Alloys; Materials Engineering; Industrial and Production Engineering